ANALISIS KUALITAS AUDIT, DEBT DEFAULT, DAN LIKUIDITAS TERHADAP OPINI AUDIT GOING CONCERN DI BURSA EFEK INDONESIA - lee, Suyanti; Purba, Mortigor Afrizal (SCIENTIA JOURNAL, 2021)
The survival of the company is a major highlight for interested parties, especially investors. Going concern audit opinion is an opinion given by the auditor to the company because there is an auditor's suspicion about the entity's ability to sustain its business. The purpose of this research is to examine the effect of audit quality, debt default, and liquidity on going concern audit opinion. The object of this research is the coal mining subsector companies listed on the Indonesia Stock Exchange for the period 2015-2019. The sample was selected by purposive sampling method with the results obtained by 10 companies. The research data uses secondary data through the website www.idx.co.id. The research method used logistic regression analysis. Testing data using the SPSS v.25 application. The results of this study indicate that audit quality partially has no effect on going concern audit opinion, while debt default and liquidity partially affect going concern audit opinion. The test results also show that the audit quality, debt default, and liquidity variables simultaneously affect going-concern audit opinion with a determination value of 70.7%, while 29.3% is influenced by other variables apart from the independent variables in this study.